Étude de souches du virus de la mosaïque du concombre (CMV) chez le melon en Tunisie et identification des génotypes résistants - M'nari, Monia; Jebari, Hager; Cherif, Christine (Cahiers Agricultures, 1993)
Virus diseases of Cucurbitaceae are a major problem in Tunisia, with Cucumber Mosaic Virus (CMV) ranking second in importance. Prospecting in northern and central of Tunisia among muskmelon (Cucumis melo L.) and fakous (Cucumis melo var. flexuosus) fields yielded CMV isolates which were used to evaluate the different pathotypes. Tunisian isolates of CMV were classified according to two methods: that of Marchoux (1975), which demonstrated the presence of group C, as well as a new variant of this group. The classification of Lecoq and Pitrat (1982) indicated the presence of «common» and «song» pathotypes. Field susceptibity of muskmelon and fakous varieties to the «common» pathotype at early stages of growth was confirmed under controlled conditions. Inoculation of muskmelon lines from different origins allowed genotypes resistant to this pathotype to be selected, i.e. : PI 161375, Ginsen makuwa and Freeman's cucumber.